Hubungan Interaksi Guru dengan Siswa Terhadap Hasil Belajar Matemtika Siswa SD Kelas V - Haslinda Haslinda; Rahmawati Patta; Abd Kadir A (Jurnal Pendidikan dan Pembelajaran Sekolah Dasar (JPPSD), 2021)
The problem in this study is the lack of teacher-student interaction so that the students' Mathematics UTS scores are low. This study is a quantitative study with a correlation design that aims to determine the relationship between teacher and student interactions on Mathematics learning outcomes for fifth grade elementary school students in cluster VI. The results showed that there was a significant relationship between teacher-student interaction and students' mathematics learning outcomes with the value of t_count(4.7026) greater (>) than the value of t_(table)(1.67591) so H0 was rejected. Based on the analysis of the data above, it can be concluded that the interaction of teachers with students in the learning process will have an impact on student learning outcomes. So the better the interaction between teachers and students, it will improve student learning outcomes. From these conclusions, the impact resulting from this study is known that good interaction between teachers and students will improve student learning outcomes